Explaining automated decision-making: a multinational study of the GDPR right to meaningful information - Dexe Jacob; Franke Ulrik; Söderlund Kasia; van Berkel Niels; Jensen Rikke Hagensby; Lepinkäinen Nea; Vaiste Juho (Association internationale pour l'étude de l'économie de l'assurance, 2022)
The General Data Protection Regulation (GDPR) establishes a right for individuals to get access to information about automated decision-making based on their personal data. However, the application of this right comes with caveats. This paper investigates how European insurance companies have navigated these obstacles. By recruiting volunteering insurance customers, requests for information about how insurance premiums are set were sent to 26 insurance companies in Denmark, Finland, The Netherlands, Poland and Sweden. Findings illustrate the practice of responding to GDPR information requests and the paper identifies possible explanations for shortcomings and omissions in the responses. The paper also adds to existing research by showing how the wordings in the different language versions of the GDPR could lead to different interpretations. Finally, the paper discusses what can reasonably be expected from explanations in consumer oriented information.